Municipal health decision-making a new institutionalist analysis of selected municipalities in the province of Bohol - Cainghog, Nelson G.
Municipalities in the province of Bohol were observed to have different performance in health policy implementation, especially in the adoption of Sentrong Sigla standards of the Department of Health and the delivery of primary health services. Several municipalities adopted at the soonest opportunity the SS standards. Some did a notch higher by aiming at establishing a primary hospital. The study aims to account for the main factors contributing to these differences in performance. To account for these, an event history analysis of SS certification using the variables number of veto players coded in terms of party affiliation, the amount of health expenditures, and the occurrence of an election year was done. A comparative analysis of two cases-successful and an attempt-complements the above quantitative analysis. The comparison uses an analytic narrative supplemented by Hilderbrand and Grindle's framework of government capacity with modifications. This investigation is guided by assumptions and propositions of new institutionalism, particularly historical and rational choice institutionalisms.The quantitative findings show that the number of veto players did not significantly matter contrary to expectation. The amount of health expenditure per se also did not matter. But together, the two variables mattered significantly.The number of veto players complements the amount of health expenditure in accounting for the timing of SS certification. Also, the occurrence of an election year did not make any significant effect. One unexpected result of the event history analysis was that two-veto player configurations are more likely to have SS certification compared to one-veto player configurations. In the qualitative aspect, there were two unexpected findings that were not anticipated by the framework of the study: the critical juncture that facilitated the creation of an infirmary in San Miguel and the tacit veto of the municipal doctor in Mabini that contributed to the non-participation of the municipality in the SS certification program. Over-all, the study provided poof, at least partially, to the insignificance of party affiliation (the basis in counting the number of veto players) in health decision-making at the local level. It also opened possible avenues for applying historical institutionalism in the analysis of successful cases. Finally, it also broke stereotypes of health officers as promoters of health programs and opened a possible area of inquiry related to the veto power of expert bureaucrats like the local public doctor. This can pave the way for a reformulation of veto players' theory at the local level.